Analisis Ketinggian Banjir di Kota Medan Tahun 2024 (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze variations in flood inundation heights in Medan City through 2024 using a quantitative approach based on Geographic Information Systems (GIS). The data used include field surveys, flood hazard maps, rainfall data, land use, and regional topography. The results show that flood heights vary between 0 and 100 cm, with distribution influenced by a combination of rainfall intensity, land use changes, drainage capacity, and topographic characteristics. The northern area of ​​the city has the highest flood heights and risk, driven by low elevation, inadequate drainage systems, and proximity to the coast and major rivers. This study emphasizes the importance of drainage management, river normalization, and spatial utilization control as effective and sustainable flood mitigation measures in Medan City. The findings of this study recommend improvements to the drainage system, river normalization, spatial utilization control, and the use of spatial data as a basis for more effective and sustainable flood mitigation planning in Medan City.